Olduvai's oldest Oldowan. Issue 150 (January 2021) - Stollhofen, Harald; Stanistreet, Ian G.; Toth, Nicholas; Schick, Kathy D.; Rodríguez-Cintas, Agata; Albert, Rosa M.; Farrugia, Paul; Njau, Jackson K.; Pante, Michael C.; Herrmann, Edward W.; Ruck, Lana; Bamford, Marion K.; et al.
Abstract: Previously, Olduvai Bed I excavations revealed Oldowan assemblages <1.85 Ma, mainly in the eastern gorge. New western gorge excavations locate a much older ∼2.0 Ma assemblage between the Coarse Feldspar Crystal Tuff (∼2.015 Ma) and Tuff IA (∼1.98 Ma) of Lower Bed I, predating the oldest eastern gorge DK assemblage below Tuff IB by ∼150 kyr. We characterize this newly discovered fossil and artifact assemblage, adding information on landscape and hominin resource use during the ∼2.3–2.0 Ma period, scarce in Oldowan sites. Assemblage lithics and bones, lithofacies boundaries, and phytolith samples were surveyed and mapped. Sedimentological facies analysis, tephrostratigraphic and sequence stratigraphic principles were applied to reconstruct paleoenvironments and sedimentary processes of sandy claystone (lake), sandstone (fluvial), and sandy diamictite (debris flow) as principal lithofacies. Artifacts, sized, weighed, categorized, were examined for petrography, retouch, and flake scar size. Taxonomic classifications and taphonomic descriptions of faunal remains were made, and phytoliths were categorized based on reference collections. Lithics are dominantly quartzite, mainly debitage and less frequently simple cores, retouched pieces, and percussors. Well-rounded spheroids and retouched flakes are rare. Identifiable taxa, Ceratotherium cf. simum (white rhinoceros) and Equus cf. oldowayensis (extinct zebra), accord with nearby open savanna grasslands, inferred from C3 grass, mixed and/or alternating with C4 grass-dominated phytolith assemblages. Palms, sedges, and dicots were also identified from phytoliths. Diatoms and sponge spicules imply nearby freshwater. The assemblage accumulated at the toe of a Ngorongoro Volcano-sourced fan-delta apron of stacked debris flows, fluvials, and tuffs, preserving fossil tree stumps and wooded grassland phytoliths farther upfan. It formed after the climax of Ngorongoro volcanic activity during a Paleolake Olduvai lowstand and was then buried and preserved by lacustrine clays, marking the first of two lake transgressions, signifying wetter climates. Orbital precessional lake cycles were superposed upon multimillennial (∼4.9 kyr) lake fluctuations. Highlights: We present a new ∼2 Ma lithics and bone assemblage from the western Olduvai Basin. The assemblage sits below the Bed I Basalt, 150, 000 a older than Upper Bed I DK site. It's the oldest evidence of Homo exploitation of a savanna paleolandscape at Olduvai. The assemblage was sited on a fan-delta toe, incised during Lake Olduvai withdrawal. It was buried by major lake transgression at the end of Ngorongoro fan progradation.